Green's functions and condensed matter - Rickayzen, G. (New York Academic press, 1980)
"Green's functions, named for the mathematician who developed them in the 1830s, possess applications in many areas of physics. This volume presents the basic theoretical formulation, followed by specific applications that include transport coefficients of a metal, the Coulomb gas, Fermi liquids, electrons and phonons, superconductivity, superfluidity, and magnetism. 1984 edition"--
Reprint of: London ; New York : Academic Press, 1980.
Includes bibliographical references and index.
Keywords: Green's functions; SCIENCE / Solid State Physics